Assessment of Perda, e-community program, Pulau Pinang. - Cheah, Fee Lian; Abu Hassan, Musa; Bolong, Jusang (Penerbit UTHM, 2011)
The purpose of this paper is to assess the e-community program launched by Penang Regional Development Authority (PERDA) based on participants. 276 survey forms were distributed randomly throughout four zones Multimedia Training Centers in Penang. Generally, the respondents admitted that PERDA’s e-community program had positive elements towards them. It was found that interpersonal source such as peers, neighbours and family members were main sources to provided information regarding PERDA’s e-community program to the respondents. The results showed that most respondents had positive attitude towards competence, ability to try and complexity of computer and the Internet after going through the program. However, there were respondents which had negative attitudes towards their ability to try using the computer and Internet after involving in this program. The results also found that features in PERDA’s ecommunity program become the core into such involvement. Therefore, efforts are needed now and then in order to enhance the quality of this program thus encouraging more participation in the future.